ISSUES OF ENSURING GENDER EQUALITY IN THE ERA OF GLOBALIZATION (International journal of artificial intelligence, 2026)
In the world, all opportunities are being created for women to increase their spiritual and cultural, social activity, and for them to have their position in society. Women are taking part in the transformation of all spheres of society's development and are gaining a worthy place in state administration. At the moment, in some cases, women are being discriminated against and pressure is being observed against their free activities. Therefore, ensuring gender equality, social protection of women's rights at the state level is gaining ideological importance.